Systemic enzyme therapy with trypsin, bromelain and rutoside in the management of arthritis: an overview - Kulkarni, Abhay P.; Bendrey, Himanshu A. (International Journal of Research in Orthopaedics, 2021)
Chronic arthritis, including osteoarthritis and rheumatoid arthritis, is a growing major public health problem leading to disability and reduced quality of life. Analgesic and anti-inflammatory drugs form the mainstay of treatment for chronic arthritis. The protracted use of the conventional medications for their management is fraught with shortcomings, including safety concerns. Proteolytic enzymes and antioxidant combinations have been used empirically, since ages, in many of these conditions. There is a growing body of evidence indicating the beneficial effects exerted by the individual ingredients and their combinations on the pathophysiology of arthritis. The analgesic, anti-inflammatory, anti-edematous, anti-thrombotic and anti-oxidant properties of these substances have been demonstrated in multiple in vitro and animal models. Furthermore, the therapeutic use of proteolytic enzyme-antioxidant combination is also supported by clinical trials in arthritis and related disorders. Such studies have mostly been carried out on preparations consisting of combinations of trypsin, bromelain and rutoside. The results of various studies (placebo-controlled and comparisons with nonsteroidal anti-inflammatory (NSAIDs) drugs) in patients with arthritis suggest that oral therapy with such enzyme-antioxidant combination produces improvement in all major clinical parameters like swelling, pain and joint stiffness and have comparable efficacy to NSAIDs. Some clinical studies also evaluated their effect on biochemical markers like cytokines, interferons and prostaglandins and reported remarkable improvements. The overall data also indicates that the tolerability of the enzyme-antioxidant combination is better than conventional therapies.